Intervention for Creating Equal Classrooms - Pinchuk, Kateryna; Zalipska, Krystyna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
Bullying and victimization are prevalent during adolescence. In Europe and North America, approximately 6% of middle school students are bulling others, and approximately 10% of middle school students are bullied 2 or 3 times in a month. Moreover, adolescence is a sensitive period for social status. LaFontana and Cillessen (2009) showed a clear peak in prioritizing status enhancement in early adolescence. Given that the CEC (Creating Equal Classroom) project aims to reduce the level of bullying through mitigating classroom status hierarchy, grade 7 is a particularly relevant developmental stage to implement this intervention project. Target population: Adolescents from grade 7 at the middle school Methods: Questionnaires, multilevel modeling with Mplus 8.0 to estimate the intervention effects due to the nested nature of data, trainings and discussions. Short description of results and conclusions: Pupils are encouraged to take responsibility for their social environment and for interacting with peers. This program is effective in reducing the frequency of adolescents’ involvement in bullying situations. With help of this program, the number of both initiators and victims of bullying will decrease.